Análisis de la influencia política del programa de entrevistas de ecuavisa, contacto directo, en los estudiantes de periodismo de la ULVR - Garzón García, María Victoria (2018)
This document presents an analysis of the political influence of the Ecuavisa interview program, Direct Contact, on the students of journalism of the ULVR, on which it is argued with the adequate literature to support the theoretical precepts, which address the role they play. the media in the construction of public opinion and what are the interests to which this responds. On this, the approach of public and private media was presented, in reference to the fact that both respond to their own interests, the former to economic and political interests, and the latter to the interests of electoral calculations and social manipulation for political acceptance; so it is estimated that journalistic principles are currently in crisis………